How to Harmonize the Ethnic Nose - Grinfeld, Artur; Betelli, Rodrigo; Arruda, Guilherme; Almeida, Washington (Facial Plastic Surgery, 2016)
The demand for cosmetic surgery has significantly increased in the past few years mainly due to economic rise witnessed in Brazil. The state of Bahia has predominately Afro-descendant population with the same countrywide scenario, where the surgeon must be able to face challenges such as the specifics demands of rhinoplasty in an ethnic nose. It represents not only a different nasal variety from the Caucasoid, but also a complex anatomical feature, with its own peculiarities, as thicker and oilier skin, with bulky fibrous fatty tissue with numerous sebaceous glands. The nose tip features both inadequate projection and definition, including a short columella and underdeveloped nasal spine. The lower lateral cartilages are lower and thinner if compared with Caucasian noses. The nasal septum is short and fragile, whereas the dorsum is low and wide with deep nasion and wide obtuse angles between nasal bones. Finally, yet importantly, the nose base has increased interalar distance and excess of alar wing, with an ovoid, horizontal, and open nostril. Considering all these uniqueness, the existing challenges to approach an ethnic nose are clear. It requires skill and accurate surgical maneuvers to seek facial harmony while maintaining the characteristics that define the individual ethnicity and identity.
Keywords: ethnic; nose; rhinoplasty